METHODICAL APPROACH TO THE COMPARATIVE EVALUATION OF ARMORED SPECIAL VEHICLES HOUSING MATERIALS - Mykhailo O. Shyshanov; Volodymyr I. Kotsiuruba; Ivan P. Datsenko; Valentyn P. Sakhno; Ihor I. Derkach (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
Based on the analysis of experience with the panzer specialized vehicles and requirements for the protection of this group of material, it‘s suggested the methodological approach for the comparative evaluation of materials for their buildings, which ensures the necessary level of the protection from the effects of damaging factors, to optimize the choice on the basis of the financial cost, quality characteristics and manufacturing technology. In the article as the baseline approach for comparison the armored vehicles body materials buildings, the method of progressive standard has proposed to use.